Internalisasi nilai pendidikan Islam dalam membentuk etika digital siswa ditengah budaya global serba instan - Mulia Sopiandi Harahap; Firza Alkhori; Herlini Puspika Sari (Jurnal Pendidikan Agama Islam, 2026)
The rapid advancement of digital technology has significantly transformed students’ patterns of social interaction, particularly in their engagement with digital media. Within the context of an increasingly instant global culture, various issues related to digital ethics, such as the spread of misinformation, cyberbullying, and impolite communication, are becoming more prevalent among students. This study aims to examine the role of internalizing Islamic educational values in shaping students’ digital ethics in response to these digital cultural challenges. The research employs a qualitative approach using library research by analyzing a range of literature sources, including books, scholarly journal articles, and previous studies relevant to Islamic education, digital ethics, and student character development. The collected data were examined through descriptive analysis to explore the relationship between Islamic educational values and students’ ethical behavior in digital environments. The findings indicate that Islamic values such as honesty, responsibility, politeness, and the principle of tabayyun play a significant role in fostering students’ awareness of digital ethics. Therefore, the internalization of Islamic educational values can serve as a strategic approach to developing a generation that not only possesses strong digital literacy but also demonstrates moral integrity in using technology in a responsible and ethical manne